An intensive care approach to posterior reversible encephalopathy syndrome (PRES): An analysis of 7 cases - Demirel, Ismail; Kavak, Burcn Salih; Ozer, Ayse B.; Bayar, Mustafa K.; Erhan, Omer L. (Galenos Yayincilik, 2014)
Objective: The aim of this study was to retrospectively evaluate the intensive care unit treatments applied to obstetrics patients with a diagnosis of posterior reversible encephalopathy syndrome (PRES). Material and Methods: The cases of 7 pregnant patients who had been diagnosed with PRES between July 2011 and July 2013 were retrospectively reviewed. The patients' clinical data, brain magnetic resonance imaging (MRI) images before and after treatment, and neuropsychological tests were evaluated. Results: Five out of 7 patients had eclampsia, 1 patient had severe preeclampsia, and 1 patient developed HELLP syndrome secondary to PRES. Calcium channel blockers and beta-blockers were used as antihypertensive treatment. All patients were treated with parenteral magnesium sulfate. In addition, sodium thiopental was given to control sedation and convulsions in all patients except 1. The neurological and radiological findings of all cases treated in the intensive care unit improved. Conclusion: Posterior reversible encephalopathy syndrome is a clinical condition with a multifactorial etiology and can result in different clinical findings. Radiological imaging techniques can be used for the diagnosis of PRES. Pregnancy and the postpartum period often lead to this syndrome. In some cases, PRES can cause irreversible neurological deficits or death. For patients with severe radiological findings, early diagnosis and thiopental infusion, in addition to treatment with antihypertensive agents and magnesium sulfate, may lead to quicker and more effective recovery from clinical manifestations. We suggest supplementation of standard treatment with early thiopental infusion.
Keywords: PRES; intensive care unit; obstetrics patient